A Needs Assessment of New York State Veterans: Final Report to the New York State Health Foundation - Schell, Terry L. (Rand Health Q, 2011)
Mental health disorders and other types of impairments resulting from deployment experiences are beginning to emerge, but fundamental gaps remain in our knowledge about the needs of veterans returning from Iraq and Afghanistan, the services available to meet those needs, and the experiences of veterans who have tried to use these services. This article highlights the findings of a study focused directly on the veterans living in New York state. The study included veterans who currently use U.S. Department of Veterans Affairs (VA) services as well as those who do not; and it looked at needs across a broad range of domains. The authors collected information and advice from a series of qualitative interviews with veterans of Operation Iraqi Freedom (OIF)/Operation Enduring Freedom (OEF) residing in New York, as well as their family members. In addition, they conducted a quantitative assessment of the needs of veterans and their spouses from a sample that is broadly representative of OEF/OIF veterans in New York state. Finally, they conducted a review the services currently available in New York state for veterans. The study found substantially elevated rates of post-traumatic stress disorder (PTSD) and major depression among veterans. It also found that both VA and non-VA services are critically important for addressing veterans' needs, and that the health care systems that serve veterans are extremely complicated. Addressing veterans' mental health needs will require a multipronged approach: reducing barriers to seeking treatment; improving the sustainment of, or adherence to, treatment; and improving the quality of the services being delivered. Finally, veterans have other serious needs besides mental health care and would benefit from a broad range of services.